2013
DOI: 10.1097/01.sa.0000435572.01496.5c
|View full text |Cite
|
Sign up to set email alerts
|

High-Frequency Oscillation for Acute Respiratory Distress Syndrome

Abstract: with HFOV at the 3 analysis points (94, 300, and 500 patients), increased need for vasoactive drugs suggesting a mechanism of harm not offset by better oxygenation and lung recruitment, and the likelihood that HFOV would not decrease death rates. Continued enrollment would have put patients at risk with little posibility of benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
6

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 0 publications
2
38
0
6
Order By: Relevance
“…Two large RCTs evaluating routine HFOV in moderatesevere ARDS have been recently published [384,385]. One trial was stopped early because the mortality was higher in patients randomized to HFOV [384].…”
Section: We Recommend Against Using High-frequency Oscillatory Ventilmentioning
confidence: 99%
“…Two large RCTs evaluating routine HFOV in moderatesevere ARDS have been recently published [384,385]. One trial was stopped early because the mortality was higher in patients randomized to HFOV [384].…”
Section: We Recommend Against Using High-frequency Oscillatory Ventilmentioning
confidence: 99%
“…A survival benefit, however, has not been demonstrated with HFOV. In one randomized clinical trial, Young et al 35 found no significant difference between conventional ventilation and HFOV. Ferguson et al 36 randomly assigned adults with new-onset, moderate to severe ARDS to HFOV or to a control strategy targeting lung recruitment with the use of low V T and high PEEP.…”
Section: Types Of Recruitment Maneuversmentioning
confidence: 98%
“…The authors of both studies reported satisfactory performance of these instruments in the respective patient populations. However, asking patients to complete these measures around the time of recruitment (commonly taken as the baseline measurement) into randomised controlled trials conducted within emergency and critical care settings can be problematic; patients are commonly incapacitated and unable to provide a self-assessment of their health status at or around the time of randomisation [13], [14]. Problems also arise because the event of interest is often acute in nature rather than pre-planned; the unknown timing makes it difficult to collect baseline data from participants during the occurrence of the event and at the point of recruitment into the trial.…”
Section: Introductionmentioning
confidence: 99%